Երիտթուրքական շարժումը և հնչակյանները (XIX դ. վերջ – XX դ. սկիզբ) - Հովհաննիսյան, Գեղամ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В конце XIX века, на пике национально-освободительного движения армянского народа против султанского режима, развернулось движение турецкой оппозиции, впоследствии названное движением младотурок, стремившихся утвердить в стране конституционный строй и направить Турцию в русло европейского развития. Реально осознавая, что для достижения поставленной цели собственных сил недостаточно, руководители движения пытались добиться согласия с политическими организациями подданных народов Османской империи, в том числе с армянскими организациями, вставшими на путь борьбы против османской тирании. На этом этапе обсуждение гнчакистами рассматриваемых вопросов с младотурецкими лидерами показало, что последние не признают необходимость осуществления реформ в Западной Армении и фактически отрицают наличие Армянского вопроса. At the end of the 19th century, during the rise of the national liberation movement of the Armenian people, the movement of the Young Turks – the Turkish opposition forces, was launched against the sultanate regime. The Young Turks sought to establish a constitutional, parliamentary order and put the country on a European path of development. Realizing that their forces were not sufficient to achieve this goal, the leaders of the movement tried to reach an agreement and cooperate with the subject peoples of the Ottoman Empire, including the political organizations of the Armenian people, who were fighting against the Sultanate tyranny. Numerous meetings and discussions of the Hnchakyan party figures with the Young Turk leaders during the mentioned period showed that the latter did not recognize the need for reforms in Western Armenia, did not actually recognize the existence of the Armenian Question and were led by the idea of assimilating the subject peoples of the Ottoman Empire among the Turks and creating one Ottoman nation.
Keywords: Պատմություն